PERGULATAN HUKUM DAN POLITIK DALAM LEGISLASI UU NO. 21 TAHUN 2008 TENTANG PERBANKAN SYARI’AH - Ghofur, Abdul (Faculty of Shariah and Law, State Islamic University (UIN) Walisongo, 2013)
This study intends to analyze the historical background of the enactment of Law No. 21 of 2008 concerning Islamic Banking in the perspective of relationship between law and political power. This study are considered attractive in the context of Indonesia as a state law that the majority of the population is Muslim, which is ethically Islamic law becomes an important part in the law development. Politically, the Indonesian government also has a historical background of the harmonious relationship with the Islamic forces. Determination of law No. 21 of 2008 concerning Sharia banking is not free from the constellation and political configurations that occured at that time. However, despite decorated by strict political configuration, the determination of this statue has a accountability of its juridical basis, sociological, and philosophical. Determination This law proves that Islamic law has become one of the sources of national law and has the opportunity to contribute to the development of national laws optimally in the future.